Nonlinear dynamics of four-wave mixing, cascaded stimulated Raman scattering and self Q-switching in a common-cavity ytterbium/Raman random fiber laser. (February 2021) - Lin, Shengtao; Wang, Zinan; Li, Jiaqi; Chen, Siqi; Rao, Yunjiang; Peng, Gangding; Gomes, Anderson S.L.
Highlights: The FWM is generated in standard SMF with watt-level CW pumping. Cascaded SRS, FWM and self-pulsation is simultaneously observed in this setup. The links between these nonlinear optical dynamics are also analyzed. Our lasing structure would be an ideal testbed for managing nonlinear dynamics. Abstract: The combined effect of stimulated Raman scattering (SRS), four-wave mixing (FWM) and self-pulsation in optical fibers can be either beneficial or detrimental, depending upon a specific application. In this work, we report for the first time that, under watt-level CW pumping in a common-cavity Ytterbium/Raman random fiber laser, a significant wavelength down-conversion is generated by FWM in a standard single-mode fiber; moreover, nonlinear optical dynamics of SRS, FWM and self-pulsation was simultaneously observed in this setup. In a certain range of pump powers, strong and stable self-pulsation effects were observed, which occurred simultaneously with the cascaded SRS emissions and an intense visible orange emission at 603 nm, which can be attributed to the FWM from the 1064 nm light-wave. The experimental results agree well with the theoretical calculations for the FWM process. Besides, self-pulsation and high order cascaded are also analyzed. The importance of these results for high power Raman based fiber lasers and random fiber lasers, as well as continuum generation will be discussed.